Adoption of Web 2.0 in African National Libraries: An Evaluative Study - Kannikaparameshwari, G.; Chandrashekar, M. (Journal of Information and Knowledge, 2018)
Purpose: This paper aims to provide an overall picture of the application of Web 2.0 technologies in national libraries in African countries. The focus of the research was to examine the types of Web 2.0 technologies that were used in national library websites and their features. Design/methodology/Approach: Content analysis was used in terms of quantitative approach. A checklist as the main research instrument was developed based on other checklists and questionnaires. Data were collected by accessing National library Web sites of African countries. Findings: In the African continent out of 61 countries 51 countries have national libraries. 31 of these have web presence and 10 national libraries are using Web 2.0 technologies in their websites. Research limitations: A combination of content analysis with survey and / or interview may enable future researchers to analyze other aspects (e.g. the application of internal wikis or the use of instant messaging for reference services) of Web 2.0 that a single method of content analysis could not gain. This study explores the application of Web 2.0 and is useful for all types of national libraries in evaluating/deploying Web 2.0.